Invasive Alien Plants An Ecological Appraisal for the Indian Subcontinent - Bhatt, J.R (CABI, 2014)
The Earth's flora is dynamic and has been constantly changing over a period of time. Changes may be natural or human-aided, although in the recent past the latter has played a vital role. In fact, the movement of plants from one part of the earth to the other has become very common and fre- quent owing to better trade and transport facilities. Plant species that move from one geographical region to the other (either accidentally or intentionally), establish and proliferate there and threaten native ecosystems, habitats and species are known as invasive alien plants (hereafter referred to as invasive plants) (Richardson et al., 2000). The problem of invasive plants has become global and is largely human-aided (Vitousek et al., 1997). Invasive plants are responsible for global environmental changes, bio- diversity crisis, species endangerment and disruption of ecosystem processes essential for human welfare (Drake et al., 1989; Parker et al., 1999; Mack et al., 2000; Mooney, 2005; Charles and Dukes, 2007; Herron et al., 2007, Pejchar and Mooney, 2009). The impact of invasive plants on global biodiversity is second only to habitat fragmentation and is a major global issue.